2015
DOI: 10.1038/nature14570
|View full text |Cite
|
Sign up to set email alerts
|

Long-range energy transport in single supramolecular nanofibres at room temperature

Abstract: Efficient transport of excitation energy over long distances is a key process in light-harvesting systems, as well as in molecular electronics. However, in synthetic disordered organic materials, the exciton diffusion length is typically only around 10 nanometres (refs 4, 5), or about 50 nanometres in exceptional cases, a distance that is largely determined by the probability laws of incoherent exciton hopping. Only for highly ordered organic systems has the transport of excitation energy over macroscopic dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
327
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(343 citation statements)
references
References 32 publications
15
327
1
Order By: Relevance
“…4 Recent studies, however, have shown that an efficient singlet exciton migration can occur in highly ordered supramolecular materials. [6][7][8] In particular, Sung et al. have shown by ultrafast transient fluorescence spectroscopy that in helical π-stacks of perylene bisimides delocalized excitons are initially formed and move coherently along the chain in tens of femtoseconds prior to the excimer formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recent studies, however, have shown that an efficient singlet exciton migration can occur in highly ordered supramolecular materials. [6][7][8] In particular, Sung et al. have shown by ultrafast transient fluorescence spectroscopy that in helical π-stacks of perylene bisimides delocalized excitons are initially formed and move coherently along the chain in tens of femtoseconds prior to the excimer formation.…”
Section: Introductionmentioning
confidence: 99%
“…6 Haedler et al have demonstrated that one-dimensional self-assembled nanofibers, based on carbonylbridged triarylamine building blocks, are able to efficiently transport singlet excitons over more than 4 μm at room temperature by means of a predominantly coherent mechanism. 7 Heechul et al have obtained a tunable light-harvesting material, based on a selfassembled chromophore network controlled by a genetically-engineered virus template, which has exhibited enhanced exciton transport via a partially coherent regime. 8 These recent examples clearly highlight the growing interest for obtaining controllable molecular materials for potential nanophotonic and quantum information applications where excitons move beyond the incoherent transport regime.…”
Section: Introductionmentioning
confidence: 99%
“…Not only can nanostructure morphology be controlled through judicious molecular design, 4 but it is also well-established that chromophore arrays can facilitate manybody interactions, such as resonant energy transfer, making them attractive candidates for artificial photosynthesis. 5 However, the majority of photocatalysis investigations to date that involved organic chromophores were done with the molecules fully dissolved in solution. 6−8 In order to move forward with designing artificial systems based on chromophore arrays that can be considered photocatalytic materials, a detailed understanding of how intermolecular coupling modes and environmental effects impact their performance is required.…”
Section: Introductionmentioning
confidence: 99%
“…Quasi-particles with such tunnelling properties also arise in experiments probing excitonic energy transfer in molecular crystals [49], molecular aggregates [50], photo-sythetic complexes [51][52][53][54][55][56][57], artificial light-harvesting materials [58], and ensembles of Rydberg atoms [32,59]. The long-range tunnelling amplitudes are known to have a significant effect on the dynamical properties of quantum particles in lattice po-tentials [60][61][62][63][64][65][66]. In particular, the long-range tunnelling events may substantially decrease the mixing or hitting times of the corresponding quantum walkers.…”
Section: Introductionmentioning
confidence: 99%